Suggested Model for Ensuring Systematic Exploitation of Knowledge: An Exploratory Study of the Higher Education and Scientific Research Sector - Benameur , DAHININE; Wassila , BENSAHEL (The Arab Journal of Administration, 2018)
This work aims to understand how we can achieve a systematic and conscious exploitation of knowledge, through the identification of key factors that influence the process of knowledge creation and accumulation in a sector, and its quick or slow orientation towards an effective implementation of this knowledge in the various fields of economic development. The proposed research model combines indeed three factors of considerable importance: The first factor is related to the nature of the knowledge base of the sector that allows fast or slow orientation towards an effective accumulation of knowledge and its application in the acceleration of innovation and technological progress. The second factor is related to the nature of the competitive environment and how we can take advantage of external effects (externalities) as well as knowledge spillovers and their relationship to the level of incentive for innovation. The third factor highlights the importance of systematic proximity in supporting collaboration synergies and exploiting agglomeration effects resulting from localized sources of technology to implement positioning strategies, where the possibility of accumulation of scientific knowledge is available. By choosing the higher education and scientific research sector as a field of application, we conclude the inability of this model to give an appropriate representation of the specificity of the systematic knowledge exploitation in this sector, this led us to formulate some research proposals on how we can adopt a development approach for improving the use of knowledge accumulated in this sector and its investment in the realization of economic performance.